Health care workers and AIDS: a differential study of beliefs and affects associated with accidental exposure to blood - Rissi Maria Rosa Rodrigues; Machado Alcyone Artioli; Figueiredo Marco Antonio de Castro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
This study aimed to analyze affective and cognitive determinants of the professional work of individuals caring for patients with HIV/AIDS, in view of the risk and/or experience of accidental exposure to blood. We drew on the theoretical-methodological references of Fishbein & Ajzen and Maslow's theory. Fifty health care workers were evaluated using an attitudes questionnaire and a needs and motivations instrument. The research verified differences between answers by health care workers who had never suffered accidents and those who had already experienced accidental exposure to blood. Health care workers did their work activities motivated by the need for self-fulfillment and valued their own performance when they were able to meet the patients' emotional needs. Among health professionals who had never experienced accidental exposure to blood, the predominant beliefs was that patients feel remorse over having expose themselves to HIV. Accidental exposure to blood raises difficulties in personal life. Technical aspects are also associated with the possibility of accidental exposure to blood.